Gender evaluation methodology for Internet and ICTS: A learning tool for change and empowerment. - Cinco, Cheekay; Garcia Ramilo, Chat (Association for Progressive Communications, APC Women's Networking Support Programme, 2005)
GEM is not only a tool for gender evaluations. Nor is it just a guide or a manual that breaks down gender concepts and makes it relevant for ICT projects. GEM is also a project and a community. GEM as a project germinated in January 2000. A workshop, held in a small Manila hotel in the Philippines, was the seed that grew into a fouryear undertaking. About 30 women, mostly members of APC WNSP, reflected on almost 10 years of women’s networking in an attempt to build a collective understanding of the real impact of our work in changing women’s lives. But instead of arriving at definitive answers, we ended up asking more questions about change, empowerment and ICTs. What changes are empowering for women? how do these changes shift gender relations between women and men? how can we tell if ICTs are making a difference in these changes? how do we measure these changes? These questions led to months of research, meetings and painstaking writing. At that time, evaluations of ICT projects were very hard to come by. Evaluation tools for ICT projects were only beginning to be explored, mainly through the work of the International Development Research Centre which was developing an evaluation framework for ICTs for development projects. APC WNSP provided the gender related perspective in this endeavour through proposals around building gender considerations in evaluation frameworks that were largely gender neutral.
Keywords: 2000 à aujourd'hui; méthodologie; outils; ouvrages de références; projet charge mentale; pédagogie; périodes historiques; ressource en ligne; technologie; thématiques